التدفق النفسي وعلاقته بالصحة النفسية لدى معلمي التربية الخاصة - العروم، اسماء, جحيدر، رميصاء (جامعة الوادي university of Eloued, 2022)
الملخص: هدفت الدراسة الحالية الى الكشف عن طبيعة العلاقة بين التدفق النفسي والصحة النفسية لدى عينة من معلمي التربية الخاصة بولاية الوادي, وهذا من خلال التعرف على مستوى المتغيرين لدى العينة, وقد تم الاعتماد على المنهج الوصفي الارتباطي لأنه الأنسب لهذه الدراسة كما سعت الى دراسة مدى دلالة الفروق في كل منهما تبعا للجنس والاقدمية في العمل. حيث تم جمع بيانات الدراسة بالاعتماد على مقياس التدفق النفسي الذي عدد بنوده 36 ومقياس الصحة النفسية المتكون من56 بند. تم تطبيق المقياسين على عينة قوامها 55 من معلمي التربية الخاصة وتم اختيارهم بطريقة قصدية. بعدها تم معالجة البيانات إحصائيا وهذا بالاعتماد على الأساليب الإحصائية معامل ارتباط بيرسون, واختبار "ت" للكشف على دلالة الفروق واختبار تحليل التباين fللكشف على دلالة الارتباط بين التدفق النفسي والصحة النفسية. وكانت النتائج كالتالي: - لا توجد علاقة ارتباطية دالة إحصائيا عند مستوى الدلالة( ) بين التدفق النفسي والصحة النفسية لدى معلمي التربية الخاصة. -لا توجد فروق دالة إحصائيا عند مستوى الدلالة ( ) بين الإناث والذكور من معلمي التربية الخاصة على مقياس التدفق النفسي. - لا توجد فروق دالة احصائيا عند مستوى الدلالة ( ) بين الاناث والذكور من معلمي التربية الخاصة على مقياس الصحة النفسية. - لا توجد فروق دالة إحصائيا عند مستوى الدلالة ( ) بين معلمي التربية الخاصة على مقياس التدفق النفسي تبعا للأقدمية (اقل من 10 سنوات / 10 سنوات فأكثر). - لا توجد فروق دالة إحصائيا عند مستوى الدلالة ( ) بين معلمي التربية الخاصة على مقياس الصحة النفسية تبعا للأقدمية (اقل من 10 سنوات / 10 سنوات فأكثر). وفي الأخير فسرنا النتائج استنادا للإطار النظري والدراسات السابقة في الموضوع. وفي الأخير قمنا بتقديم مقترحات أو توصيات آفاق البحث الميداني في الموضوع مستقبلا Résumé :فرنسية أو انجلزية The current study aims to reveal the nature of the relationship between psychological influx and mental health among a sample of private educational teachers in Wilaya of El-Oued. And this is by identifying the level of the two variables in the sample, the descriptive correlative approach was relied on. Because it is the most appropriate for this study, as it required to study the significance of the differences. Each of them is according to gender and precedence at work, where the study data were collected based on the psychological flow scale, which has 36 items, and the mental health scale, which consists of 56 items. The two scales were applied to a sample of 55 special education teachers who were chosen intentionally. Then, the data were processed statistically, and this was based on statistical methods, Pearson correlation coefficient, and “t” test to detect the significance of the differences and the analysis of variance test f to detect the significance of the correlation between psychological flow and mental health. The results were as follows: -There is no statistically significant correlation at the level of significanc ( (between psychological flow and mental health of special education teachers. -There are no statistically significant differences at the level of significance ( ) between female and male special education teachers on the psychological flow scale. -There are no statistically significant differences at the level of significance ( ) between female and male special education teachers on the mental health scale. -There are no statistically significant differences at the level of significance ( ) between special education teachers on the psychological flow scale according to seniority (less than 10 years/10 years and more(. -There are no statistically significant differences at the level of significance ( ) between special education teachers on the mental health scale according to seniority (less than 10 years/10 years and more). Finally, we interpreted the results based on the theoretical framework and previous studies on the subject. In the end, we presented suggestions or recommendations for future field research prospects
دراسة ميدانية بمراكز التربية الخاصة بولاية الوادي
مذكرة ماستر علوم التربية تخصص إرشاد وتوجيه
Keywords: التدفق النفسي، الصحة النفسية; Flux psychologique, santé mentale; Psychological flow, mental health